An ambiguous clinical presentation of a gingival plasma cell granuloma - A case report - Areeba Shahid; Priya Singh; Neeta Misra; Deepak Umapathy (Wolters Kluwer Medknow Publications, 2021)
Plasma cell granuloma (PCG) is a rare localized benign proliferation of polyclonal mature plasma cells. The etiopathogenesis of the PCG remains inexplicit. Although it primarily occurs in the lungs, intraoral variants, involving the gingiva, tongue, buccal mucosa, have been reported too. Here we report a case of a 19-year-old female patient with mandibular anterior gingival exophytic growth that gave an impression of pyogenic granuloma clinically. The overgrown tissue was excised and histological examination revealed inflammatory cell infiltrate containing sheets of plasma cells. This case highlights the presence of a PCG having a periodontal origin. As intraoral occurrences of PCG are uncommon, such observations should be well documented and added to the existing literature. Advanced investigations such as immunohistochemistry can be done, which rule out the possibility of any malignancy, as seen in cases of plasmacytoma that mimic PCG (no malignant potential).